Relationship Between Posttraumatic Stress Disorder, Death Anxiety, and Insomnia in Adults After the Earthquake - Ciftci, Necmettin; Yildiz, Metin; Ucar, Mehmet (Sage Publications Inc, 2024)
This study aimed to determine the relationship between posttraumatic stress disorder, death anxiety, and insomnia in adults after the earthquake. This study, designed in a relational-cross-sectional-descriptive model, was conducted with 624 adult individuals living in a province affected by the earthquake that occurred in Turkey on February 6, 2023. The study data were collected using a personal information form, Posttraumatic Stress Disorder Checklist, Turkish Death Anxiety Scale, and Bergen Insomnia Scale. The analysis of the study data was performed by using SPSS 25.0, AMOS 24.0, and G*Power 3.1 Statistical package software. A significant positive correlation was found between posttraumatic stress disorder and Insomnia and Death Anxiety (p < .05). There was a significant positive correlation between Death Anxiety and Insomnia (p < .05). It was determined that Death Anxiety has a mediating role in the impact of posttraumatic stress disorder on insomnia (95% Confidence Interval: 0.572/1.407) (p < .05). It was determined that the model created in line with the hypotheses was compatible and the model fit indices were within the desired limits, with x(2)/df = 1.795, RMSEA = 0.03, CFI = 0.95, GFI = 0.946, AGFI = 0.93, IFI = 0.95. It was determined that posttraumatic stress disorder increased death anxiety and insomnia after the earthquake. Conducting longitudinal studies on the post-earthquake period is recommended.
Keywords: earthquake; death anxiety; posttraumatic stress; insomnia